Technical guidance on mental toughness in achieving final match results for students in the Special Sports Class (KKO) - Purwanto, Sugeng; Sujarwo, Sujarwo; Supriyanto, Agus; Wibowo, Yuyun Ari (Darmabakti: Jurnal Pengabdian kepada Masyarakat, 2025)
Mental toughness is a set of attitudes, values, behaviors, and emotions that enable an individual to survive, face various obstacles or pressures that are felt, and achieve the desired goals. Special Sports Class (KKO) is a co-curricular activity intended to increase students' interest and talent to become potential athletes in the future. There are various factors related to mental toughness, such as self-development through challenges, sports awareness of students, how students' attitudes or behavior when facing pressure, and the desire or enthusiasm of students in reaching the match. According to interviews with several KKO students, 70% of KKO students do not understand mental toughness, so it is necessary to provide technical guidance related to it. This community service activity was carried out thanks to the collaboration of lecturers from the Faculty of Sport and Health Sciences (FIKK), Universitas Negeri Yogyakarta (UNY) as resource persons and those in charge of the KKO Class of State Junior High School (SMPN) I Kalasan, Sleman Regency. The activity was carried out in theory and practice on July 10-11, 2024, at SMPN I Kalasan with the participants of all students, coaches, and sports teachers who handle KKO at SMPN 1 Kalasan, totaling 50 people, consisting of 6 coaches, two sports teachers, and 42 KKO students. The results of this activity show that 92% of KKO students need mental toughness guidance in facing matches, and the remaining 8% of KKO students need further mental toughness guidance assistance in facing matches.